A comparative study on laser-assisted and conventional machining characteristics of waspaloy - Hamidreza Esrafili; Hossein Amirabadi; Javad Akbari; Farshid Jafarian (Journal of Materials Research and Technology)
Waspaloy is a nickel-based superalloy primarily used in the manufacture of compressor discs and shafts. In this study, a comparative analysis was performed on Laser-Assisted Machining (LAM) and Conventional Machining (CM) of waspaloy to evaluate the surface alterations and machining characteristics at the various process conditions. To investigate the impact of laser beam heat beneath the workpiece surface, an initial scan was conducted without applying a cutting depth. This was done using different cutting speed and feed rate settings while keeping the laser parameters constant. The heat-affected layers (HAZ) were then analyzed, followed by the machining process. Subsequently, the cutting forces, machining temperature, surface roughness, and microhardness variations were analyzed between the LAM and CM processes. The results revealed that under laser scanning conditions, the highest temperature recorded at the laser–workpiece contact point was 729 °C, whereas in the LAM process, this temperature increased to 778 °C. Additionally, the findings showed that the presence of a Secondary HAZ resulted in higher machining forces in the LAM process, with one exception, compared to CM. The maximum cutting force in laser-assisted machining was 499 N, while for CM, it was 460 N. In LAM, the chip temperature ranged from 189 to 541 °C, while in CM, it varied from 104 to 349 °C. Surface roughness improved by up to 3.82 times in the LAM process compared to CM. Moreover, the results indicated that microhardness variations in LAM were more consistent than those observed in CM.